2020
DOI: 10.1149/1945-7111/ab995f
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-Multi-Walled Carbon Nanotubes/Glassy Carbon Electrode as an Efficient Sensing Platform for Promethazine

Abstract: A sensor based on polyethylenimine-functionalized multi-walled carbon nanotubes/glassy carbon electrode (fMWCNT-PEI/GCE) was developed for promethazine hydrochloride (PMZ) detection in pharmaceutical samples. PMZ is oxidized at the modified electrode at more negative potentials and with higher sensitivity than at the bare electrode. The morphological characterization of the sensor surface showed a homogeneous layer with size distribution of the diameters of the PEI-fMWCNT ranging from 22-47 nm. The characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…22 Polyethyleneimine-functionalized carbon nanotubes (PEI-CNTs) have shown efficiency in technological applications such as solar cells, 23 removal of pollutants, 24 and an excellent electrochemical sensing platform for silver nanoparticles, 25 chromium ions, 26 and promethazine hydrochloride. 27 Nevertheless, it has been little explored for detecting heavy metal ions and even less regarding the PEI-CNT/GO composites. In particular, Huang et al reported an electrochemical sensor using a glassy carbon electrode (GCE) modified with three-dimensional GO-CNT hybrid nanocomposite for the simultaneous detection of Pb 2+ and Cd 2+ ions using anodic stripping voltammetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Polyethyleneimine-functionalized carbon nanotubes (PEI-CNTs) have shown efficiency in technological applications such as solar cells, 23 removal of pollutants, 24 and an excellent electrochemical sensing platform for silver nanoparticles, 25 chromium ions, 26 and promethazine hydrochloride. 27 Nevertheless, it has been little explored for detecting heavy metal ions and even less regarding the PEI-CNT/GO composites. In particular, Huang et al reported an electrochemical sensor using a glassy carbon electrode (GCE) modified with three-dimensional GO-CNT hybrid nanocomposite for the simultaneous detection of Pb 2+ and Cd 2+ ions using anodic stripping voltammetry.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, PEI is widely known for its chelating metal properties; after the functionalization of CNTs with PEI, it allows the possibility of introducing active sites in CNTs for heavy metal adsorption . Polyethyleneimine-functionalized carbon nanotubes (PEI-CNTs) have shown efficiency in technological applications such as solar cells, removal of pollutants, and an excellent electrochemical sensing platform for silver nanoparticles, chromium ions, and promethazine hydrochloride . Nevertheless, it has been little explored for detecting heavy metal ions and even less regarding the PEI-CNT/GO composites.…”
Section: Introductionmentioning
confidence: 99%
“…27 A study on promethazine hydrochloride (PZC) is aimed at as a drug being used in large quantities. 28 PZC is a phenothiazine group of drugs implied for treating problems like nausea, vomiting, motion sickness etc. 29 These problems are cured by the action of PZC acting as receptor antagonist of mACh receptor further leading to blockage of acetylcholine action mechanism over receptors and reducing these causes.…”
mentioning
confidence: 99%
“…Beside, previous electrochemical sensors use graphite or glassy carbon as support for electrode materials in the molecular detection and also require a polymer binder to prevent the electrode material from falling off. 17,18 So, there is a possibility to limit the contact area between the electrode and active material. Consequently, it causes of lower sensitivity and less stability of the sensors.…”
mentioning
confidence: 99%